Tigers in the highlands? Profile of the Puno business community - Tapia, Percy (1996)
In recent years the city of Juliaca has grown surprisingly. Almost a quarter of a million people inhabit it, 40,000 tricycles go through it daily, ingenuity and commerce add up perfectly. The growth of Juliaca is probably the best sign of the magnitude of the changes that have taken place in the department of Puno. It is very striking to see how entrepreneurs emerged in a relatively young city and to discover what strategies they adopted, as well as to know what the main characteristics of these entrepreneurs are. These are the questions that, in general, motivated this work.